The development of dramatic symbolism and satire in the plays of Zakes Mda on the realities of South Africa’s political situation - Uwah, Chijioke; Muller, Roy (University of the Free State, 2003)
This article examines Mda’s artistic development, specifically in his use of symbolism and satire, while considering reasons why he chose to use these devices. The analysis will cover the period from the seventies, when he wrote some of his earlier plays, to the nineties, when some of his unpublished plays were produced. This will be done with a view to establishing the continuity or otherwise of his use of these dramatic devices from his early days to the present.

In die artikel word Mda se artistieke ontwikkeling van nader bekyk, spesifiek wat betref sy gebruik van simboliek en satire asook die moontlike redes waarom die dramaturg hom tot die gebruik van hierdie middele gewend het. Die ontleding dek die tydperk vanaf die sewentigerjare toe hy van sy vroeëre dramas geskryf het tot die negentigerjare toe van sy ongepubliseerde stukke opgevoer is. Dit word gedoen ten einde die kontinuïteit, al dan nie, in sy gebruik van hierdie dramatiese middele in die vroeër tot die onlangse dramas te bepaal.
Keywords: Mda, Zakes; Satire; Symbolism; Artistic development; Playwriter